Investigation into optical nanolithography employing wavefront engineering techniques and evanescent waves interference - Chua, Jeun Kee (2010)
Optical lithography is an important process in the realization and advancement of nanotechnology. This thesis proposes and investigates potential approaches to ameliorate process issues associated to patterning at high resolution as well as to achieve patterning resolution beyond fundamental limitation. In optical projection lithography, the process window indicates process robustness which will deteriorate significantly, especially when the targeted resolution becomes sub-100nm. A quantitative approach is proposed as a more cost effective and time efficient alternative to commercial simulators to identify the most ideal co-employment scheme of wavefront engineering based on resolution enhancement techniques in terms of process window results. The quantitative approach proposed is based on analysing the power distribution of the zero and first orders of the diffracted source images. Employments of different process conditions of attenuated phase shift masking and off-axis illumination are simulated. The corresponding results suggest that the proposed approach approximates the process window results more accurately than a geometrical analysis approach reported previously. Experimental process window results obtained are analysed and compared to that of the proposed approach. Good correlation between the two is observed. The laser interference lithography has been employed for cost-effective simulation of optical projection lithography to facilitate research investigations related to the latter.